Existensi Perpustakaan dalam Meningkatkan Minat Baca Siswa Tentang Pendidikan Agama Islam di SLTPN 2 Plosokaten - huda, nur (Ali Muchasan, 2016)
Research Problem is How existensi library in the improving interest reading of the studen about education religion of Islam in SLTPN 2 Plosoklaten? The purpose of research: (1)To know clearly how existensi library in SLTPN 2 Plosoklaten. (2) To know what the effortdone the library into inproving Interest Reading of The Student About Education Religion Of Islam in SLTPN 2 Plosoklaten Kediri. (3) To know what the factor which to supporting and the adding library into Improving Interest Reading of The Student About Education Religion Of Islam in SLTPN 2 Plosoklaten. The procedure of research: The method used in this research is using descriptive qualitative approach. The collecting of data use observation, interviews and documentation. The source of from words and actions of the respondents. The analyst data using technik deductive. Output of this research : (1) Existensi the library of SLTPN 2 Plosoklaten, this mouth the library silent the visitor, because lak of the staff of library, the books collection is not complete, and the doceration of room is not interesting. The increase of interest reading until 15 % from year a go to now. (2) The efforts of library into inproving Interest Reading of The Student About Education Religion Of Islam in SLTPN 2 Plosoklaten on the big line are giving the best service to the visitor, to adding the books collection every year, to introduct that there library, to arranging the room to more interest.(3)the factor is supporting into inproving Interest Reading of The Student About Education Religion Of Islam in SLTPN 2 Plosoklaten are there is exixtence of fund to add the books collection althaought limited, there cooperation from teacher and headmaster, while the factor of resisitor are limited of fund owner, awareness to read is minim, influence the friendship is hight. The implication of this research that the library every support ang to help into inproving Interest Reading of The Student About Education Religion Of Islam in SLTPN 2 Plosoklaten Kediri.